3D‐Bioassembly of VH‐Spheroids for Cartilage Regeneration: in Vitro Evaluation of Chondrogenesis, Fusion and Lateral Integration (Adv. Mater. Interfaces 31/2022). Issue 31 (3rd November 2022) - Veenendaal, Laura; Longoni, Alessia; Hooper, Gary J.; Lim, Khoon S.; Woodfield, Tim B. F.; Lindberg, Gabriella C. J.
Abstract : Cartilage Regeneration Self‐assembled vitreous humor (VH) spheroids fulfill key requirements as reproducible building blocks for 3D‐bioassembly of cartilage tissues. As described by Gabriella C. J. Lindberg and colleagues in article number 2200882, these VH hydrogels promote both cellular migration and neo‐tissue formation in the active interface region of the assembloids, driving successful lateral fusion and integration between mature cartilage spheres while enabling fabrication of larger, clinically relevant, tissue constructs.